Respostas

2014-09-04T01:02:26-03:00
A) (y=0)y= x - 9 ⇒ 0= x - 9 ⇒x = 9
 (y>0)  x - 9 > 0 ⇒ x > 9
(y<0) x - 9 < 0 ⇒ x< 9

b) (y=0) -5x + 20 = 0 ⇒ -5x = - 20 ⇒ x= -20/-5 ⇒ x = 4
(y>0)  -5x + 20 > 0 ⇒ -5x > - 20 *(-1) ⇒ 5x < 20 ⇒ x < 20/5 ⇒ x< 4
(y<0) -5x + 20 < 0 ⇒ -5x < - 20 *(-1) ⇒ 5x > 20 ⇒ x> 20/5 ⇒ x> 4

c) (y=0) 1/4x + 5 = 0 ⇒1 + 20x = 0 ⇒ x= -1/20
(y>0) 1/4x + 5 > 0 ⇒ 1 + 20x > 0 ⇒ x< -1/20
  

d) (y=0) -2x + 6 = 0 ⇒ -2x = -6 *(-1) ⇒ 2x=6 ⇒x= 6/2 ⇒ x=3
  (y>0) -2x + 6 > 0 ⇒ -2x > -6 *(-1) ⇒ 2x < 6 ⇒ x< 6/2 ⇒ x<3
(y<0) -2x + 6 < 0 ⇒ -2x < -6 *(1-) ⇒ 2x > 6 ⇒ x> 6/2 ⇒ x>3


1 1 1
no item c me enrolei, tenho que rever inequações